Modeling and Simulation Support for System of Systems Engineering Applications - Rainey, Larry B.; Tolk, Andreas (Hoboken : Wiley, 2015)
Features a comprehensive treatment on the use of modeling and simulation support for system of systems engineering as well as best practices in the industryModeling and Simulation Support for System of Systems Engineering Applications provides a comprehensive overview of the underlying theory, methods, and solutions in modeling and simulation support for system of systems engineering. Highlighting plentiful multidisciplinary applications of modeling and simulation, the book addresses the criteria and challenges found within the field. Beginning with a foundation of concepts, terms, and categor.
Chapter 8 An Agent-Oriented Perspective on System of Systems for Multiple Domains8.1 INTRODUCTION; 8.2 FROM LARGE-SCALE SYSTEMS TO SoS: MAIN M & S ISSUES; 8.3 M & S APPROACHES FOR SoS; 8.4 AN AGENT-ORIENTED PERSPECTIVE FOR SoS; 8.5 EXPLOITING THE AGENT-ORIENTED PERSPECTIVE: APPLICATION EXAMPLES IN MULTIPLE DOMAINS; 8.6 CONCLUSIONS AND FUTURE WORKS; REFERENCES; Chapter 9 Building Analytical Support for Homeland Security; 9.1 INTRODUCTION; 9.2 HOMELAND SECURITY AND SYSTEM OF SYSTEMS; 9.3 MODELING, SIMULATION, AND ANALYSIS FOR HOMELAND SECURITY; 9.4 KNOWLEDGE SHARING FRAMEWORK.
9.5 a prototype system of systems application.
Includes bibliographical references at the end of each chapters and index.
Print version record.
Keywords: Systems engineering -- Data processing; Engineering models; Engineering models; Engineering; Systems engineering -- Data processing; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; Engineering models; Systems engineering -- Data processing; Electronic books; Electronic books